MRI evaluation of post-mastectomy irradiated breast implants: prevalence and analysis of complications. Issue 9 (September 2015) - Rella, L.; Telegrafo, M.; Nardone, A.; Milella, A.; Ianora, A.A. Stabile; Lioce, M.; Angelelli, G.; Moschetta, M.
Abstract : Aim: To evaluate the effect of post-mastectomy radiation therapy (RT) on breast implants as detected by magnetic resonance imaging (MRI) searching for short-term complications. Materials and methods: One hundred and forty patients (total of 144 implants) were evaluated by MRI; 80 (group 1) had undergone RT, whereas the remaining 60 patients (group 2) underwent mastectomy with implant reconstruction without RT. Two radiologists evaluated MRI images searching for implant rupture signs, sub-capsular seromas, capsular contracture, soft-tissue oedema, peri-implant fluid collections. Implant ruptures were classified as severe complications; seromas and capsular contractures as moderate complications; oedema and fluid collections as mild complications. The prevalence of MRI findings in the two groups was calculated and compared by unpaired t -test. Cohen's kappa statistics was used to assess interobserver agreement. Results: Sixty-nine out of 144 (48%) implants presented pathological findings at MRI with complication rates of 47.5 and 48.4 for groups 1 and 2, respectively. Two (5%) severe complications, 10 (26%) moderate complications, and 26 (69%) mild complications occurred in group 1 and surgical treatment was performed in 10 cases. Two (6%) severe complications, seven (23%) moderate complications, and 22 (71%) mild complications occurred in group 2 and surgical treatment was performed in eight cases. No significant difference between the two groups was found ( p> 0.1). Almost perfect agreement between the two radiologists was found for MRI image detection (k=0.86). Conclusion: RT does not seem to cause a significant effect on breast implants in terms of complication rate in patients undergoing implant-based breast reconstruction. One-stage immediate implant-based breast reconstruction performed at the same time as mastectomy could be proposed. Highlights: RT could increase complication rates of implant-based breast reconstruction (IBR). No general consensus exists in the medical literature in this field. MRI represents the gold standard imaging tool for evaluating implant integrity. Our study reports no significant early effect of RT on IBR.